Penerapan Ghadhul Bashar di Era Digital dalam Kehidupan sebagai Generasi Z : Studi Kasus di Dusun IV Panton-Pangkalan Susu - Arbiyansyah Al Fajar; Muhammad Saleh; Kamaliah R (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This study examines the implementation of Ghadhdhul Bashar (lowering one's gaze) in the life of Generation Z in the digital era, focusing on the youth of Dusun IV Panton, Pangkalan Susu. The study addresses the phenomenon of increasing free association and access to digital content that contradicts Islamic principles, such as unsupervised interactions between opposite genders. The research aims to explore Generation Z's behavioral patterns toward digital media and social interactions, as well as to evaluate the application of Ghadhdhul Bashar values as an educational solution. The study employs a qualitative approach using interviews, observations, and literature reviews as data collection techniques. The findings reveal that the implementation of Ghadhdhul Bashar is still minimal due to a lack of religious understanding, the influence of social media, and weak environmental control. This study recommends an educational approach based on Islamic values and increased collective awareness as a strategy to implement Islamic principles in the digital era.